Job stress and family work conflict on job satisfaction through nurses’ psychological well-being - Laksono, Rudy Dwi; Sanusi, Anwar; Arifin, Syaiful (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to describe and analyze the effect of work stress, family work conflict, job satisfaction and psychological well-being on Army Hospital nurses in West Java. This research uses a partial least square structural equation model to answer problem formulations and test hypotheses. In this study, the partial least square structural equation model was used to determine the direct and indirect influence of independent variables, namely work stress variables (X1) and family work conflict variables (X2) through intervening variables, namely psychological well-being variables (Y1) on dependent variables, namely job satisfaction variables (Y2). The results of this study show that descriptive analyses can be concluded involving the majority of married honorary women with significant work experience, revealing the importance of understanding the dynamics of stress and conflict in improving psychological well-being and job satisfaction. The findings emphasize the importance of intervention strategies that focus on work-family balance and stress management to support worker well-being, especially among female workers in flexible staffing conditions.